The Research and Engineering Practice in Air Clearance of Valve Hall and DC Field in VSC-HVDC Converter Station with High Voltage and Large Capacity. Issue 4 (August 2019) - Zhang, Libin; Chen, Xiangyu; Fu, Shouqiang; Li, Hongjian; Zhao, Min
Abstract: The value of air clearance is an important basis for the design of the converter station, which affects the layout and safe operation of the converter station. In this paper, the calculation method of minimum air clearance based on improved clearance shape coefficient is proposed, and the g-parameter method is used to correct the discharge characteristics of air gap under non-standard meteorological conditions. The method is applied to the valve hall and DC field air clearance design of Zhangbei ±500 kV flexible DC converter station. The Zhangbei converter station is used as a typical representative to empirically analyze the influence of temperature and humidity changes on the air gap, and we can get the temperature and humidity value when air clearance are at the maximum value, and we calculate the air clearance of different gap shape coefficients. This paper can provide method guidance and data for the selection of air clearance for other similar projects.